Numerical study of soot particles from low temperature combustion of engine fueled with diesel fuel and unsaturation biodiesel fuels. (1st February 2018) - Zhao, Feiyang; Yang, Wenming; Yu, Wenbin; Li, Han; Sim, Yu Yun; Liu, Teng; Tay, Kun Lin
Highlights: Engine combustion was numerical studied with a quad-component biodiesel mechanism. Less soot exhausted from biodiesel fuel engine combustion than that fueled with diesel fuel. Biodiesel fuel with higher fraction of unsaturated FAMEs produces more soot precursor. Abstract: In this study, numerical analysis of fuel structures on engine soot particles' mass and size were done by CFD combustion modelling using diesel and different levels of unsaturated biodiesel fuels through the KIVA4-CHEMKIN platform. The proposed numerical approach, with a quad-component skeletal mechanism of biodiesel blend surrogates along with a multi-step phenomenological soot particle model, could capture the soot particle characteristics of test fuels with acceptable accuracy under engine combustion conditions. The reduction of exhaust soot from biodiesel combustion, compared to diesel fuel, was attributed to the suppressed soot precursors formation and lower number of particles in total. However, it was concluded that the biodiesel fuel with a higher fraction of unsaturated FAMEs (more double carbon bonds CC) contributed more to the formation of soot precursors, thus producing a higher amount of soot particles in mass and numbers as a consequence of accelerated soot particle nucleation and soot surface growth.